2005
DOI: 10.1158/1078-0432.ccr-05-1189
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Estrogen-Regulated Gene, EIG121, Induced by Hormone Replacement Therapy and Differentially Expressed in Type I and Type II Endometrial Cancer

Abstract: Purpose:The identification of genes and pathways that are affected by estrogenization may shed light on the mechanisms of estrogen action. Here, we describe the expression pattern of a novel estrogen-induced gene, EIG121, in distinct types of endometrial cancer. Experimental Design: EIG121was identified by cDNA microarray analysis of endometrial RNA from women receiving either placebo or estrogen replacement therapy. The expression level of EIG121 was then measured by real-time quantitative reverse transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 30 publications
1
53
0
Order By: Relevance
“…26 Similarly, we have previously reported that Premarin treatment significantly induced the endometrial tissue expression of the novel estrogenregulated gene, EIG121. 7 In contrast, Premarin and depot MPA caused only slight differences in the endometrial tissue expression of S100A4 compared with baseline; these differences were not statistically significant (Figure 3). Similarly, S100A4 expression does not show differential expression in the estrogen-dominant proliferative phase endometrium compared with the progesterone-dominant secretory endometrium (data not shown).…”
Section: S100a4 Expression In Relationship To Exogenous Hormones and mentioning
confidence: 88%
See 2 more Smart Citations
“…26 Similarly, we have previously reported that Premarin treatment significantly induced the endometrial tissue expression of the novel estrogenregulated gene, EIG121. 7 In contrast, Premarin and depot MPA caused only slight differences in the endometrial tissue expression of S100A4 compared with baseline; these differences were not statistically significant (Figure 3). Similarly, S100A4 expression does not show differential expression in the estrogen-dominant proliferative phase endometrium compared with the progesterone-dominant secretory endometrium (data not shown).…”
Section: S100a4 Expression In Relationship To Exogenous Hormones and mentioning
confidence: 88%
“…21 Gene expression was analyzed in human endometrial biopsies from two different clinical trials involving hormonal therapy. In the first group, described previously, 7 healthy, postmenopausal women received Premarin (Wyeth Research), 0.625 mg/ day p.o., for 3 months. In the second group, healthy, premenopausal women received depot medroxyprogesterone acetate (depot MPA; Pharmacia & Upjohn), 150 mg i.m.…”
Section: Human Normal Endometrial Biopsies Tumor Samples and Cell Lmentioning
confidence: 99%
See 1 more Smart Citation
“…KIAA1324 gene, also known as EIG121 (estrogen-induced gene 121), encodes a 1,013 amino acid (a.a.) transmembrane protein that is highly conserved among species (21). The correlation between KIAA1324 expression and prognosis in endometrial, ovarian, and pancreatic cancer patients was previously reported (21)(22)(23), but the role of KIAA1324 in gastric cancer has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Realtime reverse-transcriptase-polymerase-chain-reaction (RT-PCR) assays were performed with whole RNA extracted from tumor specimens (obtained from 46 patients) or liver specimens (from 10 patients and 10 mice) with the use of primer sets specific for human interleukin-6 and murine or human thrombopoietin, respectively, as previously described. 9,14,15 Proliferation index and microvessel density were evaluated by staining for Ki67 and CD31 antigens, respectively. 16,17 Dual immunofluorescence staining for CD31 and desmin and for CD31 and terminal deoxynucleotidyl transferase dUTP biotin nick end labeling (TUNEL) was used to assess pericyte coverage and apoptotic tumor and endothelial cells, respectively.…”
Section: Laboratory Measuresmentioning
confidence: 99%